The Effect Of Non-Financial Perspective Measurement On Financial Performance At Pt. Perkebunan Nusantara Iii (Persero) Medan - Vina Amalia Syahputri; Ova Novi Irama (Jurnal Mantik, 2022)
This study aims to determine the effect of measuring non-financial perspective on financial performance at PT. Perkebunan Nusantara III (Persero) Medan. The results of the multiple linear regression test obtained the equation Y = 0,807 + 0,228X1 + 0,234X2 + 0,503X3 + e, where measurements of customer perspective, internal business process perspective and learning and growth perspective have a significant influence on financial performance variables. The results of the correlation coefficient obtained the value of rx1x2x3y = 0,883, meaning that the measurement of customer perspective measurement, internal business process perspective and learning and growth perspective has a positive and very strong effect on financial performance at PT. Perkebunan Nusantara III (Persero) Medan. To find out whether the hypothesis is accepted or not in this study, t test (partial) and F test (simultaneous). For the results of the t test (partial) on the customer perspective variable, the value of tcount > ttable is 2,841 > 2,005, on the internal business process perspective variable, the value of tcount > ttable is 2,839 > 2,005 and on the learning and growth perspective variable, the value of tcount > ttable is 6,299 > 2,005. Thus H1, H2, and H3 are accepted because tcount > ttable. Then for the results of the F test (simultaneous) the value of Fcount > Ftable is 138,709 > 2,78. Thus H4 is accepted because Fcount > Ftable. Therefore, it can be concluded that the measurement of non-financial perspective or independent variables partially or simultaneously has a significant and positive effect on financial performance or the dependent variable at PT. Perkebunan Nusantara III (Persero) Medan.